Preliminary Observation on the Usefulness of Homoeopathic Medicine Lapis albus 30 Centesimal Potency in Hypertriglyceridaemia: A Retrospective Study - Vinitha, Edavattath Ramanan (Homœopathic Links, 2022)
Background Hypertriglyceridaemia is a clinical condition where the serum triglyceride level rises above the normal value of 150 mg/dL. It often leads to cardiovascular diseases, and severe hypertriglyceridaemia increases the risk for pancreatitis. All lipid-lowering drugs used in conventional medicines are reported to have adverse side effects. In this scenario, it is prudent to explore a drug that effectively reduces the triglyceride level, without any side effects, in a relatively shorter time. This study aimed to highlight the action of Lapis albus 30 centesimal (30C) in reducing hypertriglyceridaemia.Materials and Methods A retrospective study of case records of patients who were under medicine Lapis albus 30C for hypertriglyceridaemia, irrespective of age and gender, in outpatient department of National Homoeopathy Research Institute in Mental Health, Kerala, was done. Pre- and post-intervention fasting lipid profile values were analysed and evaluated for the study.Result There was a clinically important difference in triglyceride level after administration of Lapis albus 30C in 23 cases out of a total of 25 cases.Conclusion The present study indicates that the medicine Lapis albus 30C can be useful in reducing hypertriglyceridaemia and lends support for exploring the possibility of this medicine in a larger study sample.
Keywords: hypertriglyceridaemia; Lapis albus; calcium hexafluorosilicate